COPYRIGHT LAWS IN INDIA - Avani Maheshwari (Journal of Legal Studies & Research, 2020)
Copyright is a type of intellectual property laws and its involver giving authorship to creators of literary work which can be expressed in words, scheme, codes or any other form. It also includes musical, dramatic work, sound recordings and films. Copyright does not protect the idea but the expression of those ideas. Section 13i of the copyright act provides for protection of literary work and this right is given or vested in the owner by Section 14ii of the copyright act. The owner can only exercise this right or any other person licenced by the owner in this regard. These bundles of rights include right to publication, right to reproduction, right to adaptation, right to translation, etc. This protection is only conferred on the original work of the owner, meaning it is not copied from somewhere else. It commences from the moment when the work is created and the registration is optional. However, for better protection it is advisable to obtain registration. It is merely a prima facie proof maintained by the registrar and it does not confer rights. Section 17iii of the copyright act provides that the author of the work is the first owner. However, if an employee in the scope of employment creates any work then in that case the employer become the owner.